Language As Unifying Nation: The Existence of Digital Literacy in Countering Hoaxes - Rahmah Fauziyah; Tri Indri Hardini; Dadang Sunendar; Yulianeta Yulianeta; Khaerudin Kurniawan; Halimah Halimah (Jurnal Penelitian Pendidikan, 2022)
The role of Indonesian as a unifier of the nation is very important in everyday life. The presence of digital literacy greatly affects the acquisition of information for each individual. Students as the nation's successors who are currently faster at mastering technology obtain a lot of information. It should be noted that digital literacy is mastered by students so that it is not easy to accept hoax information. Indonesian as a unifier of the nation must be supported by digital literacy skills, especially as an effort to fight the circulating hoaxes. The use of technology for students becomes a daily activity that is rarely restricted and supervised. The convenience in the digital world also often brings information that must be investigated further. Moreover, if the hoax information received by students is disseminated it can have a bad influence on other people. Data retrieval at SMKN 13 Bandung with descriptive qualitative methods. According to students of SMKN 13 Bandung, the negative impact of hoaxes can harm many people, being wrong in taking action, misleading, causing debate, and facts are no longer believed. Indonesia as a unifying nation today needs to be accompanied by digital literacy skills. Digital literacy can equip students in using technology, evaluating, and then utilizing information in digital media properly and correctly.